2019
DOI: 10.1101/636670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient RNA-mediated reprogramming of human somatic cells to naïve pluripotency facilitated by tankyrase inhibition

Abstract: In contrast to conventional human pluripotent stem cells (hPSC) that are related to post-implantation embryo stages, naïve hPSC exhibit features of pre-implantation epiblast. Naïve hPSC are established by resetting conventional hPSC, or are derived from dissociated embryo inner cell masses. Here we investigate conditions for transgene-free reprogramming of human somatic cells to naïve pluripotency. We find that tankyrase inhibition promotes RNA-mediated induction of naïve pluripotency. We demonstrate applicati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…On the other hand, t2iLGö-naive cells also show better differentiation ability into endodermal derivatives with respect to primed ones. Correspondingly, prior works have revealed efficient induction of primitive and mature endoderm-specific markers in t2iLGö-naive hESCs and hiPSCs in vitro [ 50 , 51 ] as we obtain. Actually, a report suggests that hESCs cultured with t2iLGö-modified medium (t2iLGöY) increase their differentiation potential toward endoderm, in contrast to their primed origins [ 52 ].…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, t2iLGö-naive cells also show better differentiation ability into endodermal derivatives with respect to primed ones. Correspondingly, prior works have revealed efficient induction of primitive and mature endoderm-specific markers in t2iLGö-naive hESCs and hiPSCs in vitro [ 50 , 51 ] as we obtain. Actually, a report suggests that hESCs cultured with t2iLGö-modified medium (t2iLGöY) increase their differentiation potential toward endoderm, in contrast to their primed origins [ 52 ].…”
Section: Discussionsupporting
confidence: 53%
“…This relationship held true in 2i and at N24 and indicates that the KO of these genes perturb the operative in vivo cell state transition machinery. In general, we surmise that stalling the activity of the exit machinery is critical to in vitro capture and self-renewal of naïve stem cells, consistent with empirical requirements for signal inhibition in both mouse and human (Bredenkamp et al, 2019;Ying et al, 2008). Interestingly, deficiency for some differentiation drivers increases similarity of 2i profiles to the in vivo pre-implantation epiblast.…”
supporting
confidence: 72%
“…Klf2 may therefore be a rodent specific addition to the naïve TF-network. A further significant species difference is the very low expression of TCF7L1 in primate naïve cells, which underlies the differential responsiveness of mouse and human naïve cells to GSK3 or Wnt pathway inhibition (Bredenkamp et al, 2019;Rostovskaya et al, 2019). Klf2 is a genomic target of Tcf7l1 (Martello et al, 2012).…”
mentioning
confidence: 99%
“…Mouse ES cells self-renew efficiently in the presence of LIF and the MEK inhibitor PD0325901 (PD) alone (Dunn et al, 2014;Ying et al, 2008), whereas stable propagation of human naïve stem cells additionally requires the atypical protein kinase C inhibitor Gö6983 and blockade of the Wnt pathway (Bredenkamp et al, 2019a). We observed that when plated without feeders in PD only, a large fraction of human naïve cells differentiated within 3 days into flattened epithelial cells ( Figure 1A).…”
Section: Human Naïve Stem Cells Can Enter the Trophectoderm Lineagementioning
confidence: 99%
“…Culture conditions have now been developed (Guo et al, 2017;Takashima et al, 2014;Theunissen et al, 2014) that support self-renewal of human stem cells with transcriptome proximity to pre-implantation epiblast (Bredenkamp et al, 2019a;Nakamura et al, 2016;Stirparo et al, 2018) and other naïve features (Dong et al, 2019). Consistent with early epiblast identity, naïve stem cells do not respond directly to germ layer inductive stimuli, but must first acquire competence through a process of capacitation (Guo et al, 2017;Rostovskaya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%